Architecture for peer-to-peer databases with routing queries using ant colony algorithm and semantic support - Valêncio, Carlos Roberto [UNESP]; Costa, Leandro Rincon [UNESP]; Neto, Paulo Scarpelini [UNESP]; Cansian, Adriano Mauro [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
In a peer-to-peer network, the nodes interact with each other by sharing resources, services and information. Many applications have been developed using such networks, being a class of such applications are peer-to-peer databases. The peer-to-peer databases systems allow the sharing of unstructured data, being able to integrate data from several sources, without the need of large investments, because they are used existing repositories. However, the high flexibility and dynamicity of networks the network, as well as the absence of a centralized management of information, becomes complex the process of locating information among various participants in the network. In this context, this paper presents original contributions by a proposed architecture for a routing system that uses the Ant Colony algorithm to optimize the search for desired information supported by ontologies to add semantics to shared data, enabling integration among heterogeneous databases and the while seeking to reduce the message traffic on the network without causing losses in the amount of responses, confirmed by the improve of 22.5% in this amount. © 2011 IEEE.
Keywords: Ant colony optimisation algorithm; Distributed databases; Peer-to-peer database; Peer-to-peer networks; Routing queries; Semantics; Ant colony algorithms; Centralized management; Distributed database; Heterogeneous database; High flexibility; Message traffic; Peer to peer; Proposed architectures; Routing system; Shared data; Unstructured data; Algorithms; Database systems; Distributed computer systems; Network architecture; Peer to peer networks; Search engines; Information management